2019
DOI: 10.1186/s12909-019-1796-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between students’ perceptions of the adequacy of M1 and M2 curricula and their performance on USMLE step 1 examination

Abstract: Background Performance on United States Medical Licensing Exam® (USMLE®) Step 1 examination (Step 1) is an important milestone for medical students. It is necessary for their graduation, and selection to interview for the National Resident Match Program®. Success on Step 1 examination requires content alignment, and continuous evaluation and improvement of preclinical curriculum. The purpose of this research was to observe the association between students’ perceptions of deficits in the curricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…Perceived usefulness was found to be a major contributor to use, corroborating previous ndings that this construct is the strongest predictor of both technology adoption and technologyadoption intention (Yousafzai et al, 2007). Among medical students, perceived usefulness may arise from perceptions that the current USMLE Step 1 test-prep curriculum is inadequate (Burk-Rafel et al, 2017;Khalil et al, 2019).…”
Section: Factors Contributing To Technology Usesupporting
confidence: 77%
“…Perceived usefulness was found to be a major contributor to use, corroborating previous ndings that this construct is the strongest predictor of both technology adoption and technologyadoption intention (Yousafzai et al, 2007). Among medical students, perceived usefulness may arise from perceptions that the current USMLE Step 1 test-prep curriculum is inadequate (Burk-Rafel et al, 2017;Khalil et al, 2019).…”
Section: Factors Contributing To Technology Usesupporting
confidence: 77%
“…Critically, curricula are often developed to allow students to pass the licensing examinations, like the United States Medical Licensing Examinations (USMLEs), which may or may not emphasize an assessment of anatomical knowledge. A recent study by Khalil et al, demonstrated a correlation between students' perceptions of the curriculum and their performance on the USMLE Step 1 such that students who felt that the content of the curriculum was inadequate had lower Step 1 performances (Khalil et al, 2019). The USMLE Step 1 is usually attempted prior to clerkship and has a large focus on the basic sciences.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Interestingly, students who had higher perceptions of adequacy had better performance. 8 The perception of a meaningful learning environment, emotional climate and student-student interaction were positively associated with Step 1 performance. 9…”
Section: Pass/failmentioning
confidence: 96%